Two-dimensional correlation infrared spectroscopy reveals the detailed molecular movements during the crystallization of poly(ethylene-co-vinyl alcohol). Issue 103 (7th October 2015) - Su, Gehong; Zhou, Tao; Liu, Xifei; Zhang, Jihai; Bao, Jianjun; Zhang, Aiming
Abstract : The key role of hydrogen bonding during the crystallization of EVOH was elucidated from the enthalpy and molecular movements. Abstract : In this paper, quantitative spectroscopic evidence for the important role of hydrogen bonds during the cooling crystallization of poly(ethylene- co -vinyl alcohol) (EVOH) was successfully obtained. Furthermore, the detailed molecular movements during the crystallization of EVOH were revealed via two-dimensional correlation infrared spectroscopy. Two cooling crystallization processes were detected at 159 °C and around 101–105 °C via the combination of DSC and the newly proposed scaling-MW2D correlation FTIR spectroscopy. These two crystallization processes were defined as the primary crystallization (region I) and the secondary perfection process (region II) of EVOH. The methods for calculating the enthalpies of the pair-bonded hydrogen bonding (Δ H h ), vinyl alcohol (VA) repeating unit crystallization (Δ H C-VA ), VA repeating unit diffusion into the crystal lattice (Δ H l-VA ), and ethylene (ET) repeating unit crystallization (Δ H C-ET ) were established via van 't Hoff plots. For regions I and II, the contributions of the pair-bonded hydrogen bonding of the VA repeating units to the entire EVOH crystallization were 42.8% (Δ H h = −90.4 ± 5.2 kJ mol −1 ) and 64.6% (Δ H h = −75.8 ± 3.1 kJ mol −1 ), respectively. However, the contributions of the ET crystallization to the EVOH crystallization were 19.4% (Δ H C-ET = −41.0 ± 2.0 kJ mol −1 ) and 32.7% (Δ H C-ET = −38.3 ± 0.8 kJ mol −1 ), which were only half of the contributions of the pair-bonded hydrogen bonding. 2D correlation analysis was used to investigate the sequential order of the groups' movement in the crystallization. It was found that region I had 3 steps. The first step is the formation of the hydrogen bonds in the VA repeating unit, and the second step is the diffusion of the VA repeating unit into the crystal lattice, resulting in the primary crystallization. The third step is the ET repeating unit crystallization accompanied by the movement of the VA repeating unit without hydrogen bonding in the amorphous region. Region II had 4 steps. The first step is also the generation of the hydrogen bonds in the VA repeating unit. The second step is a local rearrangement of the lattice in the imperfect crystalline of the VA repeating unit, called the secondary perfection process. The third step is the movement of the VA repeating unit without hydrogen bonding in the amorphous region. The fourth step is the weak crystallization of the ET repeating unit at a low temperature.